2014
DOI: 10.1097/tp.0000000000000133
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Latent Tuberculosis Infection in Solid Organ Transplant Recipients Over a 10-Year Period

Abstract: A centralized referral program for LTBI therapy in transplant candidates is effective to prevent TB reactivation posttransplant. A significant proportion of liver transplant candidates and recipients do not tolerate standard LTBI therapy. Alternative therapies for these patients should be evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 28 publications
1
31
0
1
Order By: Relevance
“…Donor TST status is not generally known and it is not possible to perform a TST in the context of a donation. We are unable to validate the performance of new techniques based on the detection of gamma-interferon production in response to M. tuberculosis antigens (interferon-gamma release assays) in this population (14,17,19). Newer TB diagnostics are needed to detect the presence of TB in potential donors.…”
Section: Discussionmentioning
confidence: 96%
“…Donor TST status is not generally known and it is not possible to perform a TST in the context of a donation. We are unable to validate the performance of new techniques based on the detection of gamma-interferon production in response to M. tuberculosis antigens (interferon-gamma release assays) in this population (14,17,19). Newer TB diagnostics are needed to detect the presence of TB in potential donors.…”
Section: Discussionmentioning
confidence: 96%
“…Other comorbidities and conditions associated with LTBI reactivation are categorized as high, moderate, slightly increased, low and very low risk, depending on their associated risk factors (14). In the high-risk category are patients with chronic renal failure requiring hemodialysis (15), transplant patients on immune suppressants (16) and patients with silicosis (17), among others. At moderate risk are patients treated with tumour necrosis factor alpha (TNF-α) inhibitors (used for many autoimmune and inflammatory conditions) (18) or glucocorticoids (19), those with diabetes (all types) and recently infected children under the age of four (20).…”
Section: Latent Tuberculosis Infection and Reactivationmentioning
confidence: 99%
“…Our extensive review of the literature identified four other detailed case reports that documented the development of active TB disease after LTBI treatment . In addition, we found a total of 56/2651 (2.1%) cases of active TB among 41 observational cohorts and six RCT . Among them, only five cases were described in detail.…”
Section: Resultsmentioning
confidence: 95%
“…We found 41 cohort studies that evaluated the outcome of LTBI therapy. Eleven were from Europe, 10 from US and Asia, seven from South America, and one each from Africa, Australia, and Canada . Only nine were prospective .…”
Section: Resultsmentioning
confidence: 99%